Pyrolysis Carbonization of Sago Starch - Haryadi Wibowo; Arenst Andreas Arie; Budi Husodo Bisowarno (JURNAL INTEGRASI PROSES, 2021)
Battery requirements are increasing over time, the anode for sodium ion batteries (SIB) can use amorphous carbon. Carbon synthesis is carried out via pyrolysis. Research on the synthesis of carbon derived from sago starch is still rare. This study aims to determine the carbon characteristics of sago starch treated with nitrogen doping according to the SIB anode by taking into account the morphology, size distribution, material structure, material composition, and the distance between layers. The carbonization method used in this research is the pyrolysis process at 900 o C for 1 hour. Variations in the experiment were carried out through direct pyrolysis process with variations of urea against starch 3:1, 2:1, and pure starch. The experimental results were analysis using SEM (EDS) and XRD. The results showed that the pyrolysis process doped with nitrogen with a ratio of 3:1 urea had an interlayer distance of 0.353304 nm, 2:1 had an interlayer of 0.368059 nm, and 0.390178 nm of pure sago starch. This value indicates that carbon is a non-graphite material (> 0.3354 nm). The carbon produced from pyrolysis produces carbon that is amorphous and has a similar shape, which is like wood.